Pengaruh Sifat Machiavellian, Time Budget Pressure, Loc Pada Dysfunctional Audit Behavior, Akuntan Publik Di Bali - Pranyanita, AA Istri; Sujana, I Ketut (E-Jurnal Akuntansi, 2019)
This study aims to obtain empirical evidence regarding the effect of machiavellian properties, time budget pressure, locus of control on behavioral dysfunctional audit. The population in this study is an auditor who works in a public accounting firm in Bali with a total sample of 54 auditors, taken using a purposive sampling method. The data analysis technique used in this study is multiple linear regression analysis. The test results show that machiavellian properties, time budget pressure, and external locus of control have a positive effect on behavioral dysfunctional audit. Whereas internal locus of control has a negative effect on behavioral dysfunctional audit. One of the factors that influence this behavior deviation is internal factors, namely personal characteristics, as well as external factors that are in the outside environment of the auditor. Dysfunctional audit behavior can reduce audit quality that has an impact on the auditing profession. Keywords:  Dysfunctional audit behavior, machiavellian, time budget pressure